Performance evaluation of pharmacy x in Yogyakarta using balanced scorecard approach - ., Satibi; Furdiyanti, Nova Hasani; Rahmawati, Maya (Indonesian Journal of Pharmacy, 2007)
The research to evaluate the performance of Pharmacy X in Yogyakarta using balanced scorecard approach has been performed. The goal of the present work was to find out the performance of the Pharmacy, evaluated by four perspectives, i.e. finance, customer, internal business process, and learning and growth.This research implemented non experiment at design by evaluative descriptive approach. Data consist of primary and secondary data. The primary data was obtained from observation of prescribing service process, i.e. average of dispensing time drug information service, drug available, identification of Drug Related Problem (DRP), customer satisfaction, and interview. Secondary data is taken from pharmacy documents, i.e. pharmacy finance report, pharmacy labor, and the patients-prescription in 2003-2005.The results show that pharmacy X condition is not good. The performance of finance perspective indicated the Return on Investment in 2003-2005 was bellow the average (1,45.%, 0.% and 0.%).Net profit margin (0,80.%, 0.% and 0.%) and turn over ratio (4,86 x, 4,48 x and 3,85 x). Performance of  customer perspective indicates good customer satisfaction, but the number of prescription decreased. Learn – growth perspective analysis indicated a high level of employee motivation and productivity; Performance in internal business process perspective showed: level of drug availability 86,21%, average of dispensing time 16,97 minutes (for compounding drugs) and 4,78 minutes (for non compounding  drugs), drugs information weren’t appropriate with standard of Kepmenkes No.1027/MENKES/SK/IX/2004. Drug Related Problems identified were prescription under dose (29.%), over dose (7.%), and drugs interaction (64.%).Key words : pharmacy X, performance, balanced scorecard